Synthesis of carbon and carbon-nitrogen nanotubes using green precursor: Jatropha-derived biodiesel - Kumar R.; Yadav R.M.; Awasthi K.; Shripathi T.; Sinha A.S.K.; Tiwari R.S.; Srivastava O.N. (My University, 2025)
The jatropha-derived biodiesel, a green precursor was found to be a new and promising precursor for the synthesis of carbon nanotubes (CNTs) and carbon-nitrogen (C-N) nanotubes. The CNTs and C-N nanotubes have been synthesised by spray pyrolysis of biodiesel with ferrocene and ferrocene-acetonitrile, respectively, at elevated temperature under an argon atmosphere. The typical length and diameter of as-grown CNTs are 20 μm and 20-50 nm, respectively. The C-N nanotubes are found in bundles with effective length of ~30 μm and diameter ranging between 30 and 60 nm with bamboo-shaped morphology. The as-grown CNTs and C-N nanotubes were characterised through scanning and transmission electron microscopes, X-ray photoelectron, Raman and Fourier transform infrared spectroscopic techniques. These investigations revealed that the nanotubes synthesised by jatropha-derived biodiesel are clean from carbonaceous impurities and the bamboo compartment formations in C-N nanotubes are due to nitrogen incorporation. The nitrogen concentration in C-N nanotubes decreases with the increase in synthesis temperature. © 2013 Copyright Taylor and Francis Group, LLC.